A New Multi-Axial Functional Stress Analysis Assessing the Longevity of a Ti-6Al-4V Dental Implant Abutment Screw - Ghada H. Naguib; Ahmed O. Abougazia; Lulwa E. Al-Turki; Hisham A. Mously; Abou Bakr Hossam Hashem; Abdulghani I. Mira; Osama A. Qutub; Abdulelah M. Binmahfooz; Afaf A. Almabadi; Mohamed T. Hamed (Biomimetics)
This study investigates the impact of tightening torque (preload) and the friction coefficient on stress generation and fatigue resistance of a Ti-6Al-4V abutment screw with an internal hexagonal connection under dynamic multi-axial masticatory loads in high-cycle fatigue (HCF) conditions. A three-dimensional model of the implant–abutment assembly was simulated using ANSYS Workbench 16.2 computer aided engineering software with chewing forces ranging from 300 N to 1000 N, evaluated over 1.35 × 107 cycles, simulating 15 years of service. Results indicate that the healthy range of normal to maximal mastication forces (300–550 N) preserved the screw’s structural integrity, while higher loads (≥800 N) exceeded the Ti-6Al-4V alloy’s yield strength, indicating a risk of plastic deformation under extreme conditions. Stress peaked near the end of the occluding phase (206.5 ms), marking a critical temporal point for fatigue accumulation. Optimizing the friction coefficient (0.5 µ) and preload management improved stress distribution, minimized fatigue damage, and ensured joint stability. Masticatory forces up to 550 N were well within the abutment screw’s capacity to sustain extended service life and maintain its elastic behavior.